Economic Evaluation of Fidaxomicin for the Treatment of Clostridium Difficile Infection (C. difficile-associated diarrhoea) in Ireland - Anke van Engen; Montserrat Casamayor; Fidelma Loftus; Martin Coen; Andy Garnham; Maureen Watt; Larry Lacey (Journal of Health Economics and Outcomes Research)
**Background:** Clostridium difficile is associated with 20–30% of cases of antibiotic-associated diarrhoea. The incidence of C. difficile infection (CDI) is higher in Ireland than in other countries in Europe, and it is associated with considerable morbidity. Previously recommended standard therapeutic options were vancomycin and metronidazole, but the macrocyclic antibiotic fidaxomicin has recently been recommended for use in adults with CDI in Ireland.